2021
DOI: 10.1097/jcma.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomal irinotecan with 5-fluorouracil and folinic acid in metastatic pancreatic cancer after previous gemcitabine-based therapy: A real-world experience

Abstract: Background: Nanoliposomal irinotecan (nal-IRI), accompanied by 5-fluorouracil (5-FU) and leucovorin (LV), is an effective and safe therapy for patients in whom metastatic pancreatic ductal adenocarcinoma has progressed after gemcitabine-based chemotherapy. Our aim was to evaluate the effectiveness and safety of a nal-IRI + 5-FU/LV regimen for patients with metastatic pancreatic cancer and gemcitabine-based treatment failure in the real world. Methods: We retrospectively collected the baseline characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Second, in a previous study on the efficacy of nal-IRI/FF [ 11 ], patients who experienced no cancer progression with irinotecan treatment showed improved survival compared to those with prior cancer progression with irinotecan (mOS: 7.7 vs. 3.9 months). Smith et al [ 13 ] and Yu et al [ 14 ] showed a similar result in patients with APC who had been treated with irinotecan. Thus, we excluded patients who had received prior irinotecan-containing therapy to assess the effect of nal-IRI/FF without being confounded by the history of irinotecan administration.…”
Section: Discussionmentioning
confidence: 69%
“…Second, in a previous study on the efficacy of nal-IRI/FF [ 11 ], patients who experienced no cancer progression with irinotecan treatment showed improved survival compared to those with prior cancer progression with irinotecan (mOS: 7.7 vs. 3.9 months). Smith et al [ 13 ] and Yu et al [ 14 ] showed a similar result in patients with APC who had been treated with irinotecan. Thus, we excluded patients who had received prior irinotecan-containing therapy to assess the effect of nal-IRI/FF without being confounded by the history of irinotecan administration.…”
Section: Discussionmentioning
confidence: 69%
“…13 Pancreatic cancer is a well-known disease with the worst prognosis compared to other cancers. 14 We don’t know whether the cancer risk that occurred in nearly one-fifth of ADP patients is acceptable by the authors’ concept, but we are very concerned with this risk. Recently, prophylactic surgery for certain types of cancer, such as breast and ovarian cancers, has been re-considered.…”
mentioning
confidence: 99%
“…There are many reports on predictors of treatment-response by nal-IRI-based therapy. In particular, CAR, NLR, GPS, total bilirubin, carcinomatosis, and previous treatment with irinotecan have been significantly associated with overall survival (3)(4)(5)(6)(7)(8). However, no study has reported the risk factors for the adverse events during nal-IRI/FL treatment based on the analysis of factors other than the UGT1A1 polymorphism in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this trial result, the regulatory agency in Japan has approved the nal-IRI plus 5-FU and L-leucovorin (nal-IRI/FL) combination therapy. Particularly interesting studies focused on predictors of treatment-response by nal-IRI-based therapy in patients with pancreatic cancer have indicated that C-reactive protein/albumin ratio (CAR), neutrophil/lymphocyte ratio (NLR), Glasgow prognostic score (GPS), total bilirubin, carcinomatosis, and previous irinotecan treatment are significantly associated with overall survival (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%